The Effect of Moderate Intensity Exercise on the Secretion of IL-8 and TNF-α In Saliva as an Effort to Prevent Chronic Inflammation in Smokers (Bangladesh Journal of Medical Science, 2026)
Background Cigarettes which contain dangerous substances that trigger chronic inflammation is one of highest problem in Indonesia. Long-term smoking can disrupt the immune system and increase the risk of non-communicable diseases for example cancer. Moderate-intensity exercise, like swimming, is believed to positively assist to reducing inflammation and enhancing quality of life. Further researches are necessary to understand the beneficial impact of exercise in preventing chronic inflammation in smokers. Early detection through analysis of IL-8 and TNF-α secretion in saliva is a potential focus in efforts to prevent chronic inflammatory conditions. Objective This research is intended to assess the impact of moderateintensity exercise on the salivary secretion of IL-8 and TNF-α as a preventive measure against chronic inflammation in smokers. Methods Select research subjects who are healthy and given swimming training to measure maximum work capacity. Then the research subjects were divided into 4 groups, carried out a pretest before being given swimming treatment and a posttest after swimming by taking saliva samples using the gargling method for 2 minutes. Next, sample processing and measurement of IL-8 & TNF-α secretion. Then data analysis is carried out. Results There were significant differences between all group in IL-8 secretion (p=0.000 and p=0.005), also different in TNF-α secretion (p=0.160 and p=0.144). Conclusion: Moderate intensity exercise can decrease saliva secretion of IL-8 and TNF-α, so that can used to prevent chronic inflammation in smokers.BJMS, Vol. 25 No. 01 January’26 Page : 176-183